Identifikasi Objek Bawah Permukaan Menggunakan Metode Ground Penetrating Radar di Kompleks Candi Kedaton, Muarojambi, Indonesia - Bambang Sugiarto; G.M Lucki Junursyah; Indyo Pratomo (Jurnal Geologi dan Sumberdaya Mineral, 2018)
Ground Penetrating Radar (GPR) survey using 200 MHz frequency antenna have been conducted in July 2011 at Kedaton Temple Complex, Muarojambi, Jambi, Indonesia. The survey is aimed at providing subsurface information without digging (excavation) as in usualÂ  conventional archaeological methods. The data were collected on six lines around the main building and a courtyard inside the boundary fence of Kedaton Temple Complex. Good quality data were obtained with signal to noise ratio greater than 110 dB. The result of the subsurface model based on the electromagnetic properties of rocks generating three layers of soil, from the youngest are Layer A with a thickness of 0.26 meters to 0.78 meters, Layer B with a thickness up to 1.51 meters, and Layer C coveringthe indication of archaeological object with a thickness of 0.35 meters up to 3.87 meters. The southern part of the main building showsa delineation and spread of thick layers of soil with a total thickness up to 4.50 meters, while the northern part of ancillary buildings shows a delineation and thin layers of soil with a total thickness only 2.60 meters. The indication of archaeological objects in the sub-surface indicated by the presence of anomalous heights which has a depth varying from 1.65 meters to 4.50 meters. This is interpreted to be a sub-surface anomaly that is likely to be archaeological objects still buried. The archaeological object may represent an ancient building in the zone of depression that accumulates due to the great floods, tidal Batanghari River, and sea level fluctuation in the past.Keywords: Archaeology, geophysics, Ground Penetrating Radar (GPR), Kedaton, Muarojambi.